Sklyanin Determinant for Reflection Algebra - Rozhkovskaya, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
Reflection algebras is a class of algebras associated with integrable models with boundaries. The coefficients of Sklyanin determinant generate the center of the reflection algebra. We give a combinatorial description of Sklyanin determinant suitable for explicit computations.